The manner of urocanic acid accumulation in fish by tracking histidine ammonia lyase activity during storage of vacuum‐packed, eviscerated, and whole fish. Issue 3 (28th January 2021) - Zare, Davood; Muhammad, Kharidah; Ghazali, Hasanah Mohd
Abstract: Accumulation of urocanic acid (UCA) in stored fish has been attributed to both endogenous and exogenous histidine ammonia lyase (HAL) activity. The level of HAL in Indian mackerel, tuna, and sardine were monitored at different temperatures. It was also evaluated during storage of eviscerated and whole fish under vacuum packaging. UCA production in sardine was also evaluated during storage. The highest and the lowest activity of HAL in fresh fish was observed in Indian mackerel and tuna (26.32 and 9.94 Unit/g, respectively). Endogenous HAL was the main agent of UCA accumulation at 0°C while it was not the only effective factor. The main agent of UCA accumulation in fish depended on the kind of fish which was important during long storage at low temperatures. Results also indicated that unlike evisceration, vacuum packaging was effective on decrease and control of HAL content during storage of fish. Practical applications: The sources of histidine ammonia lyase (HAL) in stored fish have been attributed to both fish muscle (endogenous) and bacteria (exogenous). This is very important as the strategy for preservation of fish will change by each approach. The main agent of UCA accumulation in fish is the kind of fish and exogenous HAL activity showed less effect on the accumulation of UCA. Some fish such as Indian mackerel are suitable for fresh consumption while some others such as tuna are suitable for long storage. It should be mentioned that recently it has been tried to isolate some bacteria with HAL activity from fish and improve fish preservation and control UCA accumulation while the main agent is the endogenous enzyme in fish. Overall, very few reports have discussed the manner of accumulation of this biomolecule in fish during storage and finding of the present study is an effective pace for companies and industries to choose robust strategy for the preservation of fish.